Changes in Perceived Pain Severity during Interdisciplinary Treatment for Chronic Pain - John Kowal; Keith G Wilson; Celia M Geck; Peter R Henderson; Joyce L D’Eon (Pain Research and Management)
Biopsychosocial approaches to the treatment of chronic pain are founded on the principles of cognitive behavioural therapy, the basic aims of which are, among others, to identify and modify beliefs, decrease pain-related fear and avoidance of activity, and to teach adaptive coping strategies. To determine whether functional outcomes in multiple domains are improved in such settings, this retrospective study investigated patients’ reports of increased pain severity while participating in an interdisciplinary cognitive behavioural therapy-oriented outpa-tient treatment program.